DOES THE EUROPEAN DAMAGES DIRECTIVE MAKE CONSUMERS BETTER OFF?. (10th January 2018) - Buiten, Miriam C; Wijck, Peter van; Winters, Jan Kees
Abstract: In the enforcement of European competition law, both public and private actors play a role. Public enforcement dominates. Leniency programs give cartelists incentives to reveal the cartel and disclose relevant information to the competition authority. The incentives originate from a reduction in sanctions. Directive 2014/104/EU aims at removing practical obstacles to compensation for victims of infringements of EU competition law. The literature suggests that facilitating private damages actions tends to limit the effectiveness of leniency programs. If victims are able to claim compensation, the incentive to apply for leniency may vanish. In addition to the literature, this paper not only considers the effect of private damages on incentives to apply for leniency, but also explores the consequence for deterrence and consumer welfare. Specifically, this paper investigates the implications of an improvement in the claim position of victims for (1) decisions to start or continue a cartel, (2) decisions to apply for leniency, and (3) consumer welfare. Cartelists' behavior is analyzed in a dynamic setting. The paper finds that a marginal improvement in the position of victims in most cases leads to an increase in consumer welfare but not in deterrence. In some cases, it also leads to an increase in deterrence, and, in exceptional cases, makes consumers worse off because cartelists refrain from applying for leniency.